Chronic Osteoporotic Pain in Mice: Cutaneous and Deep Musculoskeletal Pain Are Partially Independent of Bone Resorption and Differentially Sensitive to Pharmacological Interventions - Miyako Suzuki; Magali Millecamps; Lina Naso; Seiji Ohtori; Chisato Mori; Laura S. Stone (Journal of Osteoporosis)
Although the pathological changes in osteoporotic bones are well established, the characterization of the osteoporotic pain and its appropriate treatment are not fully elucidated. We investigated the behavioral signs of cutaneous and deep musculoskeletal pain and physical function; time-dependent changes in bone mineral density (BMD) and the emergence of the behavioral phenotype; and the effects of pharmacological interventions having different mechanisms of action (chronic intraperitoneal administration of pamidronate [0.25 mg/kg, 5x/week for 5 weeks] versus acute treatment with intraperitoneal morphine [10 mg/kg] and pregabalin [100 mg/kg]) in a mouse model of ovariectomized or sham-operated mice 6 months following surgery. We observed reduced BMD associated with weight gain, referred cutaneous hypersensitivity, and deep musculoskeletal pain that persisted for 6 months. Chronic bisphosphonate treatment, 6 months after ovariectomy, reversed bone loss and hypersensitivity to cold, but other behavioral indices of osteoporotic pain were unchanged. While the efficacy of acute morphine on cutaneous pain was weak, pregabalin was highly effective; deep musculoskeletal pain was intractable. In conclusion, the reversal of bone loss alone is insufficient to manage pain in chronic osteoporosis. Additional treatments, both pharmacological and nonpharmacological, should be implemented to improve quality of life for osteoporosis patients.